Islamism and Muslim Support for Islamist Movement Organizations: Evidence from Indonesia - Mujani, Saiful; Liddle, R.William; Irvani, Deni (Studia Islamika, 2023)
Does ideology predict public support for Islamist movement organizations (IMOs)? This article is to reassess the extent to which ideology matters to support social movement organizations among Muslims. A previous quantitative study in Indonesia found that Islamic ideology did not explain support for IMO such as Darul Islam. We reject the finding based on new Indonesian data. We examined Muslim support for three contemporary IMOs: FPI, HTI, and ISIS, through a nationwide opinion survey. The survey explores whether Islamism as an ideology significantly contributes to support for IMOs among Muslims. We find that a majority of Indonesian Muslims do not support IMOs, and that belief in Islamism as an ideology significantly explains the support of those who do. Preference for Islamism over the 1945 Constitution and its religiously inclusive preamble, the Five Principles, predicts mass support for Islamist organizations. Islamist ideology increases support for IMOs, while a pluralist socio-religious tradition and deradicalization and moderation policies weaken it.